CONTROLLING FACTORS OF POTENTIAL EVAPOTRANSPIRATION ABOVE GRASSLAND IN HUMID AND ARID AREA - . Yanto (Journal of the Civil Engineering Forum, 2012)
Potential evapotranspiration (PET) is an importance process in water balance studies controlled by a number of meteorological factors such as temperature, wind speed, atmospheric pressure, solar radiation, vapor pressure gradient, relative humidity and biological factors such as vegetation type, canopy height and plant density that varied in time-scale and in spatial scale. Of all those variables, determining the most controlling factors of evapotranspiration in humid and arid area is of interest of this paper. Two sites representing humid and arid area i.e. Fermi Prairie site in Illinois and Audubon Research Ranch in Arizona respectively were investigated in this study.  The flux data employed in this study was acquired from Ameriflux Netwotk. Penmann-Monteith formula is employed in to estimate evapotranspiration rate in both sites. The result shows that the PET is in dependence on the considered meteorological factor such as shortwave radiation, vapor pressure, air temperature, wind speed, net radiation and vapor pressure deficit. It is also can be inferred from the analysis that PET is also strongly controlled by vegetation factors represented as stomatal resistance. Keywords: Potential evapotranspiration, Penmann-Monteith, humid, arid.